THE EFFECT OF INCOME TAX IMPOSITION ON E-COMMERCE SALES AND THE ROLE OF INFLUENCER ENDORSEMENTS ON TAX PAID ON ONLINE SOCIAL MEDIA SALES (Case Study on Registered MSMEs at the Medan Belawan Tax Office) - Jaka Syahputra; Dahrani; Eka Nurmala Sari (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study examines the effect of income tax imposition on e-commerce sales and influencer endorsements on taxes paid by MSMEs engaged in online sales through social media in Medan City. Using a quantitative approach, data were collected through questionnaires distributed to MSMEs and analyzed with Partial Least Square (PLS). The results show that the imposition of e-commerce income tax has a significant positive effect on taxes paid (t-statistic = 3.016; p-value = 0.003). Likewise, influencer endorsements significantly affect taxes paid (t-statistic = 2.705; p-value = 0.000). Together, both variables significantly influence taxes paid, as indicated by an R-Square of 0.728 and an Adjusted R-Square of 0.723, meaning that 72.3%–72.8% of the variation in taxes paid can be explained by these factors. The findings suggest that digital taxation policies and influencer-based marketing strategies not only benefit MSMEs economically but also enhance tax compliance and state revenue. The study highlights the importance of tax literacy, regulation dissemination, and digital tax administration in strengthening MSME contributions.